Screening of Fungi for the Control of Aspergillus parasiticus - Thanaboripat*, Dusanee; Sappakitjanon, Nannapat; Prommi, Luntharima; Chareonsettasilp, Sittichai (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Fungal isolates previously selected from soil [KMC 5, SRS 4, 480512 I08 (1) and 480519 I06 (3)] were screened for their ability to produce antifungal substances against aflatoxin producing Aspergillus parasiticus IMI 102566. The production of antifungal substances by these isolates was investigated in yeast extract sucrose broth under static condition. Culture filtrates of these isolates were subsequently tested against A. parasiticus on PDA. The filtrates of all isolates produced varying degrees of inhibition against A. parasiticus with the highest inhibition zone of 33.75 mm. These isolates were identified as Trichoderma and the other two isolates were Penicillium sp. Keywords: Trichoderma, Aspergillus parasiticus, aflatoxin, biocontrol * Corresponding author: Tel: 662-3298000 Fax: 662-3298412 E-mail: ktdusane@kmitl.ac.th